1996
DOI: 10.1091/mbc.7.3.369
|View full text |Cite
|
Sign up to set email alerts
|

A distinct basic fibroblast growth factor (FGF-2)/FGF receptor interaction distinguishes urokinase-type plasminogen activator induction from mitogenicity in endothelial cells.

Abstract: Basic fibroblast growth factor (FGF-2) induces cell proliferation and urokinase-type plasminogen activator (uPA) production in fetal bovine aortic endothelial GM 7373 cells. In the present paper we investigated the role of the interaction of FGF-2 with tyrosinekinase (TK) FGF receptors (FGFRs) in mediating uPA up-regulation in these cells. The results show that FGF-2 antagonists suramin, protamine, heparin, the synthetic peptide FGF-2(112-155), and a soluble form of FGFR-1 do not inhibit FGF-2-mediated uPA up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 59 publications
(65 reference statements)
0
22
0
Order By: Relevance
“…As an example, the peptide comprising the amino acid sequence FGF2 impaired the interaction of FGF2 with FGFR1 [125] and similar peptides were successfully employed to specifically deliver antiblastic drugs to FGFR-overexpressing tumor cells [126]. In addition, vaccination against FGFR1 showed antitumor activity in vivo [127] and anti-FGFR neutralizing antibodies blocked FGF2-mediated angiogenesis in vivo [113,[128][129][130].…”
Section: Preventing Fgf/fgfr/co-receptor Interactionsmentioning
confidence: 99%
“…As an example, the peptide comprising the amino acid sequence FGF2 impaired the interaction of FGF2 with FGFR1 [125] and similar peptides were successfully employed to specifically deliver antiblastic drugs to FGFR-overexpressing tumor cells [126]. In addition, vaccination against FGFR1 showed antitumor activity in vivo [127] and anti-FGFR neutralizing antibodies blocked FGF2-mediated angiogenesis in vivo [113,[128][129][130].…”
Section: Preventing Fgf/fgfr/co-receptor Interactionsmentioning
confidence: 99%
“…After 6 h, adherent cell monolayers were incubated for 2 h at 48C with 125 I-FGF2 (10 ng/ml) and its binding to high anity FGFRs was evaluated (Rusnati et al, 1996). FGF2-adherent cells showed a signi®cant reduction in the capacity to bind 125 I-FGF2 at the apical side of the cell monolayer (5+2 c.p.m./well) when compared to cells adherent to FN (151+20 c.p.m./well) or to tissue culture plastic (225+30 c.p.m./well) (n=3).…”
Section: Immobilized Fgf2 Recruits Fgfr1 In Cell-substratum Contact Smentioning
confidence: 99%
“…GM7373 cells were transfected with 91023b-¯g in association (10 : 1, wt:wt) with pCB7 according to a calcium phosphate precipitation protocol as described (Rusnati et al, 1996) and selected with 250 mg/ml of G418 (Sigma, St. Louis, MO, USA). Parallel cultures were transfected with pCEP4-¯g 1.2 and selected with 200 mg/ml of hygromycin B (Boehringer Mannheim GmbH, Mannheim).…”
Section: Cell Cultures and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of FGF-mediated signaling events appear to require FGFRs, but additional requirements involving internalization and intracellular transport of the FGF ligand have been proposed (28 -30). A role for other FGF-binding proteins in mediating FGF signaling is thus expected, since these recent reports have identified FGF receptor tyrosine kinase-independent activities of FGFs that include the stimulation of DNA synthesis (29) (29 -31) and the regulation of plasminogen activator activity (32,33). In addition, mutants of both FGF-1 and FGF-2 have revealed that the biological activities of these factors do not entirely correlate with their ability to stimulate tyrosine phosphorylation of the FGFRs (34).…”
Section: Fgf-2 Peptides That Encompass a Sequence Implicated In Fgf-2mentioning
confidence: 99%